O Património Cultural no Cinema Português: uma análise da sua presença e ausência nos filmes Capas Negras e Rasganço - Ferreira, Vítor (2012)
The Cultural Heritage has acquired over the past years a political, social and cultural centrality. On this basis it is intended to investigate of its presence or absence, as support for action in the Portuguese cinema. Another intention is to observe which role has this heritage elements in the construction of the major fiction feature films made in recent years, as well as what type of the evolution is to be noticed. The focus will be the city of Coimbra and its heritage elements, with particular focus on how their several patrimonial elements (buildings, mobile and immaterial) are portrayed and how they are used as scenography elements.